Workers go shopping in Argentina the rise of popular consumer culture - Milanesio, Natalia, 1974- (University of New Mexico, 2013)
"Dr. Milanesio examines the ways mass consumption transformed Argentina in the twentieth century in a comprehensive analysis of the relations between consumers, goods, manufacturers, advertisers, and the state during Juan Perón's reign. She examines the social and political changes that occurred when the general population became consumers of industrial goods and participants in consumption"--Provided by publisher.